Genetic diversity and signature of divergence in the genome of grapevine clones of Southern Italy varieties - Villano, Clizia; Procino, Silvia; Blaiotta, Giuseppe; Carputo, Domenico; D’Agostino, Nunzio; Di Serio, Ermanno; Fanelli, Valentina; La Notte, Pierfederico; Miazzi, Monica Marilena; Montemurro, Cinzia; Taranto, Francesca; Aversano, Riccardo (Frontiers in Plant Science, 2023)
Although sexual reproduction has resulted in an extraordinary degree of variability among cultivated grapevine (Vitis vinifera L.), spontaneous somatic mutations have further shaped the kaleidoscope of grapevine agrobiodiversity. For centuries, growers have been collecting and propagating these various selections, calling them “clones”. The objective of this work was to analyse the population structure and the genetic diversity of six grapevine varieties from Campania and Apulia considered as panels of clones. In detail, more than 130 clones were genotyped by two reduced representation sequencing methods. Inter- and intra-varietal genetic diversity was analysed using metrics such as population structure and fixation index (FST) between populations and at single loci. Varieties belonging to the same area showed high levels of genetic similarity. The obtained Single-Nucleotide Polymorphism (SNP) data were used to identify two hundred loci with divergent markers (FST ≥ 0.80) within annotated exons. Some of them were found to be associated with phenotypic plasticity, adaptation to environmental conditions and other key traits interesting and useful for grapevine breeding. The results presented here allowed to increase our knowledge about the genetic variability of valuable traditional grapevines, highlighting the need to recover these promising genetic resources, characterize them and conserve their intra-varietal diversity.